The shadow factory - Collins, Paul; Prout, Louise (Macmillan Education Australia South Yarra, 1998)
The Shadow Factory: The Ultra-Secret NSA from 9/11 to the Eavesdropping on America by James Bamford explores the history and operations of the National Security Agency (NSA) in the wake of the September 11 attacks. Bamford provides a detailed account of how the NSA evolved into a vast surveillance organization, examining its role in global eavesdropping, domestic spying, and secretive intelligence gathering. The book also investigates the balance between national security and civil liberties, offering insights into the post-9/11 expansion of government surveillance and its implications for privacy and democracy.